Performance Analysis of Self-Compacting Concrete in Earthquake-Resistant Buildings - Ghaboussi, Demuth; lee, Kim Yeh (IHSA Institute, 2025)
This research investigates the performance of Self-Compacting Concrete (SCC) in earthquake-resistant buildings, comparing its behavior with conventional concrete under seismic conditions. SCC, known for its high flowability and ability to self-compact without the need for mechanical vibration, offers several advantages in construction, including reduced labor costs, faster construction timelines, and enhanced durability. The study explores the mechanical properties of SCC, such as compressive strength, shear strength, and flexural performance, and evaluates its resistance to cracking, permeability, and environmental degradation factors critical for earthquake resilience. Through experimental analysis and case studies, the research highlights SCC's superior performance in terms of structural integrity and long-term durability, particularly in regions prone to seismic activity. The findings demonstrate that SCC not only accelerates the construction process but also improves the overall safety and longevity of earthquake-resistant structures, making it a promising material for modern, sustainable construction practices. This study concludes that SCC offers significant benefits over conventional concrete, providing a cost-effective, durable, and environmentally friendly solution for earthquake-resistant building design and construction.